2013
DOI: 10.1177/1457496913495345
|View full text |Cite
|
Sign up to set email alerts
|

Hip resurfacing arthroplasty versus large-diameter head metal-on-metal total hip arthroplasty: comparison of three Designs from the Finnish Arthroplasty Register

Abstract: Background and Aims: large headed metal-on-metal total hip arthroplasty may produce more metal ions than hip resurfacing arthroplasty. increased metal-ion levels may be associated with higher revision rates due to adverse reaction to metal debris. the purpose of our study was to compare the survivorship of three hip resurfacing arthroplasty designs with their analogous cementless large-diameter head metal-on-metal total hip arthroplasties.Material and Methods: based on data obtained from the finnish arthroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The dominant source of wear debris in MoM THA/RHA origins from the cobalt–chromium alloy bearing [46]. In THA, corrosion at the taper–trunnion junction also plays a significant role in the generation of metal-ion wear debris [47], [48], [49]. This leads to elevated serum-ion concentrations in MoM THA compared to MoM RHA [50], [51] and may also lead to high serum-ion concentrations and soft-tissue reactions with pseudotumours in MoP THA [52], [53], [54], [55].…”
Section: Discussionmentioning
confidence: 99%
“…The dominant source of wear debris in MoM THA/RHA origins from the cobalt–chromium alloy bearing [46]. In THA, corrosion at the taper–trunnion junction also plays a significant role in the generation of metal-ion wear debris [47], [48], [49]. This leads to elevated serum-ion concentrations in MoM THA compared to MoM RHA [50], [51] and may also lead to high serum-ion concentrations and soft-tissue reactions with pseudotumours in MoP THA [52], [53], [54], [55].…”
Section: Discussionmentioning
confidence: 99%
“…The predominant indications for component revision in the current series were ARMD, observed in 48% of hips revised (47 of 108), and aseptic loosening or failure of ingrowth, observed in 35% (38 of 108). There is considerable variation in published reports as to the risk of revision and ARMD incidence between different largediameter MoM THA devices as well as for the devices used in the current study (Table 3) [9,16,26,29,32,34,44,46,47,60]. Several studies have reported good survival and a low incidence of ARMD with the devices we used in this report [12,29,32,34,44,47,51,57,60,61].…”
Section: Discussionmentioning
confidence: 90%
“…Amid numerous reports of high failure rates and concerning reports with ARMD, pseudotumors, and systemic complications to metal ions [1,6,9,16,19,20,24,31,35,40,46,47,53,54,56,63,65], three large-diameter MoM devices have been voluntarily recalled by the manufacturers: the Articular Surface Replacement (ASR) by DePuy (Warsaw, IN, USA), the Durom by Zimmer (Warsaw, IN, USA), and the R3 by Smith & Nephew (Memphis, TN, USA) [64]. Published studies have reported considerable variation in frequency of ARMD and failure for large-diameter devices [9,16,26,29,32,34,44,46,47,60]. Our center previously reported a higher frequency of revision in patients with MoM THA compared with metal-on-improved polyethylene THA [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The Finnish National Registry does not have a separate code for adverse metal reaction for a mode of failure, but overall survival rates are consistent with other reports at 95% at 6 years. 16 Registry data has so far not captured a significant difference in failure rates between BHR MoM THA and resurfacing. 8,16 However, consistent with this case series, multiple authors in several countries have described series with much higher failure rates for BHR, both in resurfacing and THA, than the initial publications would suggest, and the national registries may not be capturing an underlying problem with this implant in general.…”
Section: Discussionmentioning
confidence: 99%